Using MRI to evaluate neurodevelopment in a mouse model of neonatal hypoxia - Murphy, Ronan (Trinity College Dublin. School of Medicine. Discipline of Physiology, 2025)
Neonatal hypoxia is a medical condition resulting from the deprivation of oxygen to a newborn infant lasting long enough to cause harm to the brain. It remains a serious condition that causes significant mortality (1 million neonatal deaths per year worldwide) and morbidity, including cerebral palsy, epilepsy, and learning disabilities. Current diagnostics and treatment have limitations; there is an unmet medical need to understand the pathophysiology of neonatal hypoxia to find novel diagnostic tools that can support effective therapies. This study aimed to characterise anatomical brain changes associated with a postnatal day 7 mouse model of neonatal hypoxia and to investigate their impact on neurological development and behaviour. It was observed that hypoxia-exposed pups exhibited delayed reflex development and impaired locomotion. Adolescent mice previously exposed to hypoxia demonstrated cognitive and behavioural impairments, highlighting the long-term effects of early oxygen deprivation. MRI analysis revealed hippocampal oedema, which correlated with impairments across multiple behavioural assessments. These findings provide critical insight into the pathological progression of hypoxic injury and open new avenues to diagnostic tools.
APPROVED
Keywords: neonatal hypoxia; neuroimaging; inflammation; neurodevelopment